FACTS CLARIFIED?: THE INTERWAR ESTONIAN-GERMAN-JAPANESE INTELLIGENCE COOPERATION - Shingo Masunaga (Estonian Academy of Sciences and the Institute of History, Archaeology, 2022)
This article takes up the joint Estonian-Japanese intelligence operation against the Soviet Union in the late 1930s and attempts to recreate a full picture of the operation through never-used primary sources in the Estonian National Archives. Between 1938 and 1940, the Japanese Army organized operations to infiltrate the émigré agents into the Soviet territory near Pskov, in cooperation with the Estonian intelligence service.